Covid-19 Insights and Linguistic Methods - Tan, Kim Hua; Woods, Peter; Azman, Hazita; Abdullah, Imran Ho; Hashim, Ruzy Suliza; Rahim, Hajar Abdul; Idrus, Mohd Muzhafar; Said, Nur Ehsan Mohd; Lew, Robert; Kosem, Iztok (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by WOS/Scopus/ERA